2013
DOI: 10.1088/0953-8984/26/1/015601
|View full text |Cite
|
Sign up to set email alerts
|

Valence state, hybridization and electronic band structure in the charge ordered AlV2O4

Abstract: The valence state, hybridization and electronic band structure of charge ordered AlV2O4 are investigated by measuring the electron energy loss spectra (EELS) and performing band structure calculations using the WIEN2k code. White line ratio and O K edges of V2O5, VO2, V2O3 and AlV2O4, obtained using electron energy loss spectroscopy, are analysed specifically to probe systematically the VO6 octahedra in all of them. The systematic decrease of the L2 intensity and the O K edge intensity from V(5+) in V2O5 to Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…These results were further confirmed by calculating the areal ratio of the L 3 /L 2 peak in vanadium through the SXAS patterns. [ 29 ] As exhibited in Figure 2b and Figure S9a (Supporting Information), for V 2 O 5 electrode in the Zn(OTf) 2 ‐TEP‐H 2 O electrolyte (Figure 2c; Figure S9b, Supporting Information), the ratio of L 3 /L 2 in vanadium increased significantly to 0.92 after a full discharge and decreased to 0.78 after charging to 1.6 V, which is close to the pristine value of 0.74, indicating excellent electrode reversibility. In contrast, the ratio of the L 3 /L 2 peak areas in the Zn(Otf) 2 ‐H 2 O electrolyte only slightly increased in the discharged state compared to the pristine V 2 O 5 , and this ratio did not change back to the original value after the charging process, due to severe irreversibility.…”
Section: Resultsmentioning
confidence: 99%
“…These results were further confirmed by calculating the areal ratio of the L 3 /L 2 peak in vanadium through the SXAS patterns. [ 29 ] As exhibited in Figure 2b and Figure S9a (Supporting Information), for V 2 O 5 electrode in the Zn(OTf) 2 ‐TEP‐H 2 O electrolyte (Figure 2c; Figure S9b, Supporting Information), the ratio of L 3 /L 2 in vanadium increased significantly to 0.92 after a full discharge and decreased to 0.78 after charging to 1.6 V, which is close to the pristine value of 0.74, indicating excellent electrode reversibility. In contrast, the ratio of the L 3 /L 2 peak areas in the Zn(Otf) 2 ‐H 2 O electrolyte only slightly increased in the discharged state compared to the pristine V 2 O 5 , and this ratio did not change back to the original value after the charging process, due to severe irreversibility.…”
Section: Resultsmentioning
confidence: 99%
“…The heptamer is stabilized by a strong bonding of vanadium t 2g orbitals as proposed by Horibe et al (2006). By analyzing the structural and the spectroscopic information from electron energy-loss spectra, Kalavathi et al (2014) have shown that a partial orbital occupancy may lead to a deviation from the integral valence state on all the vanadium atoms as well as to the nontrivial ordering.…”
Section: Introductionmentioning
confidence: 92%
“…In particular, the LMTO scheme and the LSDA+U exchange functional, with electron repulsion correction U varied from 2 to 6 eV, were used by Yaresko et al (2006). The more complicated GGA-based Wu-Cohen exchange functional was used in studies (Cai et al, 2010) and (Kalavathi et al, 2014) together with ultrasoft pseudopotentials scheme and fullpotential LAPW methods, respectively. In these works, it was shown that spin-polarization effects should be accounted for in order to reproduce the band structure.…”
Section: Density Functional Study Of Charge Distribution and Bondingmentioning
confidence: 99%
“…(58) The oxygen 2p states hybridize with the 3d states of vanadium in vanadium oxides where the vanadium has the valence of 5 + , and split in the ligand field into two states, therefore there is another O-K peak at 528 eV with the presence of V-L peaks. (58) It is clearly seen that the LiPON coating before cycling does not contain vanadium, and vanadium was detected in or on the coating after cycling, Figure 11b and 11d. This result indicates that the vanadium in the Li 1.1 V 3 O 8 bulk can either migrate into the LiPON coating during cycling, or perhaps dissolved V is deposited onto the LiPON from the electrolyte solution.…”
Section: Eels Of Lipon Coatingmentioning
confidence: 99%